Student-Created Videos of Climate Change Vulnerability: Opportunity for connection and care - Gina Ziervogel; Nicola Pallitt (Environmental Association of Southern Africa, 2022)
Climate change is increasingly being seen as a complex problem that requires a change in personal and practical dimensions. To support this, climate change educators need to make use of pedagogic approaches that enable students to engage in relational values of care, empathy and connection alongside understanding the problem and potential responses. Participatory approaches, whereby students engage with members of local communities to understand climate change vulnerability, have the potential to create opportunities for connection between students, communities, universities and society in theory and practice. We describe a student video project that took place in a third-year course Sustainability and the Environment in the Department of Environmental and Geographical Science at the University of Cape Town (UCT), South Africa. Students worked in groups to undertake and film a vulnerability assessment with individuals or organisations around Cape Town in relation to the city's water crisis. Their group submission, a documentary video, needed to tell a story about social vulnerability and adaptation to the water crisis. Through a carefully scaffolded process, students' reflections indicated that the vulnerability video process helped them to understand the concept of vulnerability and strengthen their care for and connection to those 'vulnerable' to climate impacts. This kind of process-oriented authentic learning experience holds potential for increasing climate change literacy that other educators might consider.